2022
DOI: 10.1039/d2cp01740g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on the reaction mechanism of UTP cyclohydrolase

Abstract: Nucleoside triphosphate cyclohydrolase (UrcA) is a critical enzyme of the uracil catabolism pathway that catalyses the two-step hydrolysis of uridine triphosphate (UTP). Although the recently resolved X-ray structure of UrcA...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This was demonstrated for the breakdown of uracil, in which the nucleoside triphosphate cyclohydrolase (UrcA) catalyzes the two-step hydrolysis of uridine triphosphate (UTP). MD simulations showed that hydrogen bond interaction helps the reaction intermediate undergo spontaneous conformation overturn in the active site of UrcA [ 72 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…This was demonstrated for the breakdown of uracil, in which the nucleoside triphosphate cyclohydrolase (UrcA) catalyzes the two-step hydrolysis of uridine triphosphate (UTP). MD simulations showed that hydrogen bond interaction helps the reaction intermediate undergo spontaneous conformation overturn in the active site of UrcA [ 72 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…Besides, in numerous zinc-dependent enzymes, such as metallo-β-lactamases and matrix metalloproteinases, zinc cations and carboxylate groups of some Asp or Glu residues in the active sites of these enzymes often collaboratively catalyze a nonradical-mediated dissociation of the C–N bond (see Schemes S4–S6). With the assistance of the flavin-dependent acyl-CoA dehydrogenase, γ-butyrobetaine undergoes a metal-independent redox-neutral transformation to produce trimethylamine through cleavage of the C–N bond (see Scheme S6). Studying and comparing these radical dependent or independent reaction mechanisms can enhance our understanding of the different chemical strategies used in different protein families.…”
Section: Introductionmentioning
confidence: 99%